2002
DOI: 10.1139/z02-203
|View full text |Cite
|
Sign up to set email alerts
|

Relative abilities to correct rolling disturbances of three morphologically different fish

Abstract: Responses of three fish species were measured following the addition of neutrally buoyant weight-float combinations that increased rolling instability. The three species were creek chub, Semotilus atromaculatus, largemouth bass, Micropterus salmoides, and bluegill, Lepomis macrochirus. Ability to correct posture was predicted to increase with fin size and body depth in the order creek chub < largemouth bass < bluegill. In a 90-s period, the least added torque causing fish to roll to 90° in response to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 16 publications
2
25
0
Order By: Relevance
“…In some cases, fish can extract energy from vortices (Liao, 2007;Liao et al, 2003a;Taguchi and Liao, 2011), but in other cases, maintaining heading in unsteady flows increases energy cost (Cotel et al, 2006;Enders et al, 2003; Roche et al, 2014). Because fish respond strongly to roll perturbations (Eidietis et al, 2002), we hypothesized that streamwise vortices would destabilize swimming fish and increase the energy cost. Here, we have shown that bluegill sunfish do indeed use more energy when forced to swim in streamwise vortices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, fish can extract energy from vortices (Liao, 2007;Liao et al, 2003a;Taguchi and Liao, 2011), but in other cases, maintaining heading in unsteady flows increases energy cost (Cotel et al, 2006;Enders et al, 2003; Roche et al, 2014). Because fish respond strongly to roll perturbations (Eidietis et al, 2002), we hypothesized that streamwise vortices would destabilize swimming fish and increase the energy cost. Here, we have shown that bluegill sunfish do indeed use more energy when forced to swim in streamwise vortices.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several groups have found increased fish abundance in areas of streams with high turbulence intensity (Smith et al, 2005;Van Zyll De Jong et al, 1997). Horizontal cylinders, in contrast, destabilize several species of fishes (Eidietis et al, 2002;Webb, 1998;Webb and Cotel, 2010). Finally, other studies have found that generalized turbulence has negative impacts on energetic demands of some fish species (Enders et al, 2003;Lupandin, 2005;Roche et al, 2014;Tritico and Cotel, 2010).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Rotational disturbances present large control problems for swimming fish (Eidietis et al, 2002;Webb, 2002;Webb, 2004). In addition, rotational perturbations are more likely to be amplified than translational perturbations (Hoerner, 1975).…”
Section: Pelvic Fin Functional Significancementioning
confidence: 99%
“…Fishes are extremely diverse. Within this diversity are various body/fin organization modes and these are believed to affect motor and stabilizing capabilities (Harris, 1937a(Harris, , 1953Moy-Thomas and Miles, 1971;Rosen, 1982;Lauder and Liem, 1983;Webb, 1998Webb, , 2004Eidietis et al, 2002;Drucker and Lauder, 2003). Studies on locomotion typically use species representative of modes, such as various dogfishes typical of less derived selachians (e.g.…”
mentioning
confidence: 99%